Long-haul northeast travel disrupts sleep and induces perceived fatigue in endurance athletes - Stevens, C. J.; Thornton, H. R.; Fowler, P. M.; Esh, C.; Taylor, L. (Frontiers in Physiology, 2018)
Introduction: Long-haul transmeridian travel is known to cause disruptions to sleep and immune status, which may increase the risk of illness.